(untitled) (SCIENCE TIME JOURNAL, 2026)
In the contemporary information society, media discourse plays a crucial role in shaping public opinion, social attitudes, and cultural values through the strategic use of linguistic and semiotic resources. This article investigates pragmatic strategies in media discourse with a particular focus on advertising texts in English and Uzbek. Drawing on a linguopragmatic, multimodal, and discourse-analytical framework, the study examines how verbal and visual elements interact to influence audience perception, evoke emotional responses, and encourage specific patterns of behavior. The analysis is based on selected examples of advertising texts, slogans, and visual imagery, allowing for a contrastive exploration of universal and culture-specific pragmatic techniques. The findings reveal that while English and Uzbek advertising discourse employs similar persuasive strategies—such as direct address, emotional appeal, and positive connotation—their realization differs significantly due to cultural norms, values, and communicative traditions. English advertisements tend to favor brevity, explicitness, and individual-oriented messaging, whereas Uzbek advertisements emphasize implicit meaning, emotional resonance, and collective cultural values. The study also highlights the importance of visual semiotics, particularly the anchoring function of text in guiding image interpretation. Overall, the research demonstrates that an integrated analysis of linguistic and visual pragmatic strategies is essential for a comprehensive understanding of advertising discourse and offers valuable insights for media studies, intercultural communication, and the development of culturally adaptive advertising practices.